Pelatihan Penggunaan Software Video Editor Sebagai Sarana Promosi Wisata Madura - Cahyani, Andharini Dwi (Jurnal Ilmiah Pangabdhi, 2022)
This training activity on the use of video editing software was held in order to improve the ability of Human Resources (HR) of members of the Madura tourism service provider association. Video editing skills are considered important, especially for media promotion of tourist attractions, be it natural tourism, cultural tourism or culinary tourism. The purpose of this community service activity is to increase the knowledge of Madura tourism service providers to promote their business. Another objective is to establish cooperation between Higher Education and the business sectors in society. The training method used was lecture and practice. The laptop used in this training are the property of each member of the association. The results of this training show that the association members, who are mostly SME entrepreneurs in the Madura tourism sector, are enthusiastic about participating in the training activities.